Concurrent vibration attenuation and low-power electricity generation in a locally resonant metastructure. (September 2022) - Khattak, Mohid Muneeb; Sugino, Christopher; Erturk, Alper
We investigate piezoelectric energy harvesting on a locally resonant metamaterial beam for concurrent power generation and bandgap formation. The mechanical resonators (small beam attachments on the main beam structure) have piezoelectric elements which are connected to electrical loads to quantify their electrical output in the locally resonant bandgap neighborhood. Electromechanical model simulations are followed by detailed experiments on a beam setup with nine resonators. The main beam is excited by an electrodynamic shaker from its base over the frequency range of0–150 Hz and the motion at the tip is measured using a laser Doppler vibrometer to extract its transmissibility frequency response. The formation of a locally resonant bandgap is confirmed and a resistor sweep is performed for the energy harvesters to capture the optimal power conditions. Individual power outputs of the harvester resonators are compared in terms of their percentage contribution to the total power output. Numerical and experimental analysis shows that, inside the locally resonant bandgap, most of the vibrational energy (and hence harvested energy) is localized near the excited base of the beam, and the majority of the total harvested power is extracted by the first few resonators.